Rheumatoid arthritis in the elderly: a study of 35 cases - Mont'Alverne,Andrea Rocha de S. (2011)
INTRODUCTION: About one third of patients develops rheumatoid arthritis (RA) after 65 years of age, a condition named EORA (elderly-onset rheumatoid arthritis). It is postulated that EORA has different features of RA in adults. OBJECTIVE: To evaluate clinical and laboratory characteristics of patients with EORA. PATIENTS AND METHODS: Retros-pective analysis of 35 patients with EORA. Variables: gender, age at diagnosis, initial presentation, affected joints, rheumatoid factor (RF), constitutional symptoms, ESR, response to initial treatment and comorbidities. RESULTS: Of 35 patients, 26 (74%) were female and 9 were (26%) men, with 74 years on average. Thirty (86%) had polyarticular onset and 5 (14%), oligoarticular. Main joints involved were hands and wrists, with involvement of shoulders in 11 (32%). Constitutional manifestations occurred in 9 (26%). RF was positive in 27 (77%), and it was greater than 100 UI/ml in 23. The mean ESR was 62 mm/h. As for the initial treatment, 26 (74%) showed satisfactory response and 5 (14%) unsatisfactory. Methotrexate was used as the first drug in 28 and in 7 we used anti-malarial drugs. All who used anti-malarial responded satisfactorily. It was impossible to evaluate the response of 4 patients due to the recent diagnosis. CONCLUSION: In this study, the relationship between women and men was similar to that found in young people, and most showed positive RF. Most had polyarticular presentation and elevated ESR, and many had constitutional symptoms and involvement of shoulders. The recognition of EORA becomes difficult in the face of many different possible diagnoses in this age group, which explains the heterogeneity of the literature data.